PERANAN HUMAS PERUSAHAAN APLIKASI TRANSPORTASI ONLINE UBER BALI DALAM MENJAGA HUBUNGAN DENGAN DRIVER - Natalia, Natasha Fera; Pascarani, Ni Nyoman Dewi; Pradipta, Ade Devia (E-Jurnal Medium, 2018)
ABSTRACT The presence of Uber in Bali raise a controversy so that the action of rejection frequently happened such as demonstration and sweeping was done by the local transportation and conventional taxi alliance. Those action of rejection often contained a violence that cause the Uber driver feel unsafe and harmed. The Uber Bali public relation hold up the role to keep the relation with their drivers as one of the stakeholders who have an important role for the company. Therefore, the study, entitled